MATERIALS OF XVI RUSSIAN FORUM WITH INTERNATIONAL PARTICIPATION IN MEMORY OF ACADEMICIAN V.I. IOFFE «IMMUNOLOGY DAYS IN ST. PETERSBURG», JUNE 5-8, 2017 (THESES NOT INCLUDED IN SPECIAL ISSUE OF THE MEDICAL IMMUNOLOGY JOURNAL, 2017, VOL. 19) (SPb RAACI, 2017)
.